Not my idea : a book about whiteness - Higginbotham, Anastasia (Ordinary terrible things., 2018)
A white child sees a TV news report of a white police officer shooting and killing a black man. "In our family, we don't see color," his mother says, but he sees the colors plain enough. An afternoon in the library's history stacks uncover the truth of white supremacy in America. Racism was not his idea and he refuses to defend it.